BDNF improves fracture healing through promoting osteoblasts proliferation and migration via trkb/akt regulated NUCKS1 expression - Weihao Meng; Xiao Meng; Chenghua Han; Yuhe Li; Xiwen Qian; Zitao Zhang (Scientific Reports)
Abstract Background Bone nonunion is a major complication in fracture treatment. Despite considerable advancements in fracture care, 5–10% of fractures result in nonunion; This demonstrates the requirement for novel molecules to enhance fracture healing. Brain-derived neurotrophic factor (BDNF) has been increasingly recognized for its role in fracture healing; however, the underlying molecular mechanisms remain unclear. Osteoblast proliferation and migration are critical to this process. The nuclear casein kinase and cyclin-dependent kinase substrate 1 gene (NUCKS1), located on human chromosome 1 at 1q32.1, encodes a 27-kDa nuclear DNA-binding protein, which influences cell proliferation, migration, and apoptosis strongly. Although NUCKS1 is implicated in various diseases, its specific role in fracture healing remains unclear. Here, we explored whether NUCKS1 participates in the BDNF-mediated fracture-healing process. Methods We assessed NUCKS1 expression in MC3T3-E1 cells and callus from closed femoral fracture mice through quantitative reverse transcription polymerase chain reaction and Western blotting. NUCKS1 inhibition in MC3T3-E1 cells in terms of migration and proliferation changes was evaluated through transwell cell migration and Cell Counting Kit-8 assays. Fracture-healing status in mice was assessed through x-ray and micro-CT imaging 2 weeks after fracture. Results BDNF promoted NUCKS1 expression in both MC3T3-E1 cells and mouse callus tissues. NUCKS1 inhibition reduced MC3T3-E1 cell proliferation and migration and impaired fracture healing in mice. Finally, suppression of TrkB expression reduces both Akt phosphorylation and NUCKS1 expression, and inhibition of Akt phosphorylation reduces NUCKS1 expression. Conclusion BDNF may enhance NUCKS1 expression through the TrkB-mediated Akt pathway, promoting osteoblast proliferation and migration and facilitating fracture healing.